IMPLEMENTATION OF THE INDEPENDENT CURRICULUM AND SELF-REGULATED LEARNING BY STUDENTS IN ISLAMIC RELIGIOUS EDUCATION AND MORAL EDUCATION SUBJECTS AT STATE SENIOR HIGH SCHOOL 5 OGAN KOMERING ULU - Asparita Asparita; Siti Maratus Solekah; Mahfudz Mahfudz (LP2M IAI Al-Khairat Pamekasan, 2025)
This study aims to analyze the implementation of the Merdeka Curriculum and its relationship with the development of students’ self-regulated learning (SRL). Employing a descriptive qualitative approach with a case study method, data were collected through in-depth interviews, participatory observation, and documentation at a senior high school in OKU Regency. The findings reveal that the Merdeka Curriculum encourages active student engagement through project-based learning, reflection, and differentiated strategies. Its implementation provides space for students to set learning goals, monitor progress, and evaluate outcomes independently. A positive correlation is found between the curriculum and the development of SRL skills, especially among students who receive strong support from teachers and their learning environment. However, disparities persist due to differences in social background and teachers’ pedagogical readiness. The study concludes that the Merdeka Curriculum holds great potential in shaping autonomous lifelong learners, provided that systemic support is strengthened through teacher training, structured reflection practices, and school-family collaboration.